Patient’s and Caregiver’s Awareness On Secondary Prevention Strategy Of Ischemic Stroke - Islam, Md Shahidul; Ahmed, Kamal; Jahan, Israt; Kamal, Mohammad Mostafa; Hossain, Md Sarwar; Arifuzzaman, Md; Mahmud, Reaz; Hasan, Mohammed Kamrul; Habib, Mansur (Journal of Dhaka Medical College, 2023)
Background: Stroke is a big problem in Bangladesh. Though the incidence of ischemic stroke is stable or increasing, mortality is gradually decreasing. As a result, questions about disability and stroke recurrence are coming forward. A successful prevention strategy for ischemic stroke depends on the patient’s and caregiver’s awareness regarding ischemic stroke. Objectives: The objective of the study was to assess the awareness of the patients and caregivers regarding the secondary prevention strategy of ischemic stroke. Materials and methods: This was a pilot study using a questionnaire developed by a literature review. This observational study was done in the department of neurology, Dhaka Medical College, Dhaka, from March 2015 to February 2018. The study subjects were interviewed face to face with a questionnaire. Results: More than half of the respondents (54.3%) thought that ongoing drugs would cure the stroke, and they were found to be unaware of reducing or controlling their risk factors. Among risk factors, only smoking (86.4%), hypertension (84.3%), lack of regular exercise (84.3%), and being overweight (81.4%) were well-known to the respondents. Conclusion: More than half of the subjects knew the drugs should be taken to cure the disease. There was no significant difference in knowledge between rural and urban people, or males and females, regarding ischemic stroke risk factors. A system of group teaching and group discussion can change the situation. J Dhaka Med Coll. 2022; 31(1) : 15-22